Optimal Computed Tomographic Arthrography Protocol for Stifle Ligamentous Structure and Menisci in Dogs - Jiwon Yoon; Gunha Hwang; Soyon An; Young Joo Kim; Tae Sung Hwang; Hee Chun Lee (Animals)
This study aims to establish an optimized CTA protocol for qualitatively evaluating the ligamentous structures and menisci of the canine stifle. CTA of the stifle joint was conducted on six healthy beagle dogs. Each dog underwent a total of nine scans to evaluate various contrast protocols. These protocols involved three different concentrations of iodine (50, 100, and 150 mgI/mL) and three different volumes of contrast media injection (0.2, 0.3, and 0.4 mL/kg). Subsequently, the acquired arthrographic images were qualitatively assessed to determine the visibility of the stifle ligaments. The quantitative evaluation of CTA revealed that the cranial and caudal cruciate ligaments were more clearly visible in groups M2 (100 mgI/mL, 0.3 mL/kg) and M3 (100 mgI/mL, 0.4 mL/kg) in comparison to S1 (50 mgI/mL, 0.2 mL/kg) and L3 (150 mgI/mL, 0.4 mL/kg). The visibility of the medial meniscus was notably lower in S1 and S2 (50 mgI/mL, 0.3 mL/kg), while the lateral meniscus exhibited reduced visibility in S1. Overall, the high contrast settings (M2, M3) generally improved the visualization of the meniscofemoral ligament, meniscotibial ligament, and the intermeniscal ligament. For optimal evaluation of the canine stifle ligament using CTA, it is recommended to use 100 mgI/mL iodine at a dosage of 0.3 mL/kg or 0.4 mL/kg.